Analisis Total Harmonic Distortion (THD) dan Arus Harmonik Akibat Penggunaan Lampu Hemat Energi (LHE) dan Light-Emitting Diode (LED) secara Kolektif Pada Jaringan Tegangan Rendah - Silalahi, Eva Magdalena; Widodo, Bambang; Purba, Robinson (Universitas Halu Oleo, 2021)
Currently, people are increasingly using energy saving lamp (LHE) and LED because of their energy saving and low power consumption. But the use of LHE and LED in large quantities can reduce the quality of electric power. This is because LHE and LED are classified as non-linear loads which are a source of harmonic distortion for low-voltage power lines. Harmonic distortion occurs due to non-linear load currents that experience distortion or defects. Based on this, this study aims to investigate the effect of the collective use of LHE and LEDs on the quality of electrical power, such as: harmonic levels, power factor, and the resulting harmonic current and voltage waveforms. The results of this study indicate that the simultaneous use of LHE and LED with a total of 60 pieces causes distortion of the current waveform with THDi of 63.97% exceeding the standard value of IEEE Std 519-2014, with dominant harmonic currents in the 3rd order with a THDi of 74% and order 5 with a THDi of 37.6% and a THDv value of 2.44%, still below the 5.0% standard of IEEE Std 519-2014. This high THDi value has a negative impact on the low PF value of 0.722, which does not meet the power factor requirements of â‰¥ 0.85 according to PLN standards. And if the true power factor (TPF) value is calculated, the TPF value is 0.608 which is lower than the PF value of 0.722. The results obtained from the Matlab simulation show conformity to the results obtained from experimental measurements in the laboratory, namely: the simulated harmonic waveform approximates the measured harmonic waveform.